2023
DOI: 10.3390/foods12050955
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Detection of Pesticide Residue (Chlorpyrifos) on Bok Choi (Brassica rapa subsp. Chinensis) Using a Portable NIR Spectrometer Coupled with a Machine Learning Approach

Abstract: The contamination of agricultural products, such as vegetables, by pesticide residues has received considerable attention worldwide. Pesticide residue on vegetables constitutes a potential risk to human health. In this study, we combined near infrared (NIR) spectroscopy with machine learning algorithms, including partial least-squares discrimination analysis (PLS-DA), support vector machine (SVM), artificial neural network (ANN), and principal component artificial neural network (PC-ANN), to identify pesticide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…These algorithms include the sufficient component artificial neural networks (PC- ), partial least-squares discriminant analysis (PLS-DA), and support vector machines (SVM). A total of 120 bok choi samples were obtained from two small conservatories that developed cultivation of internal individuals [ 46 ]. Sixty samples were allocated to each of the two treatment groups: pesticide and non-pesticide groups.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These algorithms include the sufficient component artificial neural networks (PC- ), partial least-squares discriminant analysis (PLS-DA), and support vector machines (SVM). A total of 120 bok choi samples were obtained from two small conservatories that developed cultivation of internal individuals [ 46 ]. Sixty samples were allocated to each of the two treatment groups: pesticide and non-pesticide groups.…”
Section: Resultsmentioning
confidence: 99%
“…In the analysis of an unknown dataset, 40 samples were collected, so after the sample achieved 100 % success, F1-victory. The researchers found that the proposed portable NIR spectrometer, combined with ML algorithms (PLS-DA, SVM, and PC-ANN), could detect chlorpyrifos [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations